Zingiber officinale Uncovered: Integrating Experimental and Computational Approaches to Antibacterial and Phytochemical Profiling - Abdel Moneim Elhadi Sulieman; Safa Mustafa Ibrahim; Mamdouh Alshammari; Fahad Abdulaziz; Hajo Idriss; Naimah Asid H. Alanazi; Emad M. Abdallah; Arif Jamal Siddiqui; Sohair A. M. Shommo; Arshad Jamal; Riadh Badraoui (MDPI AG, 2024)
Background: Zingiber officinale rhizome is widely cultivated in the central region of Sudan (Gezira) and data on the biological properties of this variety grown in Sudan's climate are scarce. This study aims to comprehensively analyze the antibacterial, antioxidant, phytochemical, and GC-MS properties of Zingiber officinale (ginger rhizome) to explore its potential applications. Methods and Results: The in vitro antibacterial assessment of the aqueous extract of Sudanese ginger revealed moderate activity against Staphylococcus aureus, Salmonella typhi, Pseudomonas aeruginosa, Escherichia coli, and Klebsiella pneumonia, as determined by the disc diffusion method. The inhibition zones ranged from 12.87 ± 0.11 mm to 14.5 ± 0.12 mm at 30 µg/disc. The minimum inhibitory concentration ranged from 6.25 to 25 µg/mL, while the MBC ranged from 25 to 50 µg/mL. The MBC/MIC exhibited a bactericidal effect against all tested bacteria. Phytochemical screening revealed the presence of various chemical constituents, such as saponins, flavonoids, glycosides, alkaloids, steroids, terpenoids, and the absence of tannins in Sudanese ginger rhizome. Furthermore, GC-MS analysis of ginger rhizome identified 22 chemical compounds with retention times ranging from 7.564 to 17.023 min. The identification of 22 chemical compounds through GC-MS analysis further underscores the prospect of harnessing ginger rhizome for the development of novel medications. Computational analyses showed that ginger compounds bind the Protein Data Bank (PDB) codes 1JIJ and 2QZW with high binding affinities, reaching −9.5 kcal/mol. Ginger compounds also established promising molecular interactions with some key residues, satisfactorily explaining the in vitro results and supporting the pharmacokinetic and experimental findings. Conclusions: This study lays the groundwork for future research and pharmaceutical exploration aimed at harnessing the beneficial properties of ginger rhizome for medicinal and therapeutic purposes, particularly its antimicrobial potential.